Diversification of Beneng Taro (Birak) Processing to Support Food Security Policy in Central Lombok Regency - Lalu Ahmad Murdhani; Mujahidin Mujahidin; Erfan Wahyudi; Marzuki Marzuki (Society)
Food security remains a persistent challenge in Central Lombok Regency due to climate vulnerability, land-use change, and overreliance on rice as the dominant staple crop. This study investigates the overlooked potential of Beneng taro (Xanthosoma undipes), locally known as birak, as a climate-resilient and nutritionally valuable alternative. Using a qualitative approach, the research draws on field observations, interviews with farmers and local officials, and a review of empirical and policy literature to examine the crop’s role in local food systems. Findings reveal that Beneng taro is ecologically suited to marginal lands, yet its cultivation and utilization remain marginalized in formal development agendas. The plant’s nutritional benefits, particularly its high fiber content and low glycemic index, are undermined by fragmented knowledge on detoxification techniques, mostly transmitted orally and lacking standardization. Product diversification efforts are emerging but remain isolated, constrained by limited access to technical training, micro-enterprise licenses, and market linkages. Symbolic perceptions of Beneng taro as a wild or inferior crop further inhibit its economic potential and inclusion in mainstream food discourse. The absence of institutional support, including in the Regional Medium-Term Development Plan (RPJMD) and agricultural extension services, exacerbates these challenges. Nonetheless, the plant offers significant prospects for value-added innovations such as gluten-free flour, herbal tobacco alternatives, and biodegradable textile inputs. The study concludes that unlocking the potential of Beneng taro requires coordinated interventions in policy integration, food safety education, capacity building, and branding strategies to reposition the crop as a viable contributor to sustainable food systems and rural livelihoods in Central Lombok.